2018
DOI: 10.18520/cs/v114/i01/29-33
|View full text |Cite
|
Sign up to set email alerts
|

Science-Based Mandatory Standards and the Implementation Gap:The Case of Bottled Water Regulations in India

Abstract: Science-based standards and regulation-making is not a new phenomenon in India. In fact, Indian regulatory institutions have been developing standards and evolving in multiple areas over many decades. However, even mandatory standards are not easily enforceable in several cases, and often an 'implementation gap' has been reported. The present article explores this critical aspect of regulation-making exercise in India by considering the case of bottled water. The article analyses the regulatory governance of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Mandatory national standards pushed firms to upgrade their scientific and technical apparatus to build an ‘efficient’ monitoring system to supervise water quality at the firm level. However, it has been reported that often many small firms fail to adhere to the standards prescribed by BIS, and an ‘implementation’ gap has been reported (Sharma, 2018).…”
Section: Regulatory Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Mandatory national standards pushed firms to upgrade their scientific and technical apparatus to build an ‘efficient’ monitoring system to supervise water quality at the firm level. However, it has been reported that often many small firms fail to adhere to the standards prescribed by BIS, and an ‘implementation’ gap has been reported (Sharma, 2018).…”
Section: Regulatory Decision-makingmentioning
confidence: 99%
“…The standard-setting process mostly remained outside the gaze of the academic community. Bhaduri and Sharma (2014) examined the public’s understanding of regulation-making in the context of standard-setting for bottled water quality, and Sharma (2018) examined the monitoring and implementation gaps in regulation-making, but they did not analyse the standard-setting process of BIS per se. The regulation-making process is still mostly perceived as a ‘black box’.…”
Section: Introductionmentioning
confidence: 99%